On the State of the Union - Aiyagari, S. Rao; Greenwood, Jeremy; Guner, Nezih (Journal of Political Economy, 2000)
An overlapping generations model of marriage and divorce is constructed to analyze family structure and intergenerational mobility. Agents differ by sex, marital status, and human capital. Single agents meet in a marriage market and decide whether to accept or reject proposals to wed. Married couples must decide whether to separate or not. Parents invest in their children depending on their wherewithal. A simulated version of the theoretical prototype can generate an equilibrium with a significant number of female‐headed families and a high degree of persistence in income across generations. To illustrate the model's mechanics, the effects of two antipoverty policies, namely child support and welfare, are investigated.